Adolescent aggression and violent video games: The role of moral disengagement and parental rearing patterns. (November 2020) - Li, JiaYu; Du, Qian; Gao, Xuemei
Highlights: Violent video games exposure (VVGE) was positively associated with aggression. Moral disengagement, anger and hostility played a mediating role between VVGE and adolescent aggression. The negative parental rearing patterns moderated the relationship of moral disengagement on aggression. Abstract: Based on the General Aggression Model (GAM), this study which was crosssectional explored the relationship between VVGE and aggression in Chinese adolescents, taking into account the effects of individual difference trait (i.e., moral disengagement, anger, hostility) and family situation (i.e., parental rearing patterns). The study sample consisted of 630 Chinese adolescents ( M age = 15.43 years, SD  = 1.40). Results showed that VVGE was positively associated with moral disengagement and adolescent aggression. Furthermore, when controlling for gender, moral disengagement played a partial mediating role between VVGE and adolescent aggression and physical aggression; anger and hostility played a partial mediating role between VVGE and physical aggression and a full mediating role between VVGE and verbal aggression. Father's preference and mother's denying of the parental rearing patterns moderated the relationship of moral disengagement on aggression. The findings suggest that moral disengagement, anger, hostility and parental rearing patterns may be the factors that increase in the risk of higher levels of adolescent aggression after repeated exposure violent video games.